The The Influence Of Work Engagement And Work Life Balance On Employee Performance PT. KB Financia Multi Finance Palopo Branch - Febriani, Feby; Haedar, Haedar; Patra, I Ketut (Review of Accounting and Taxation, 2024)
Abstract Purpose - This research aims to determine the influence of work involvement and work-life balance on employee performance at PT. KB Financia Multi Finance Palopo Branch. The research method used was multiple linear regression using 58 employees of PT. KB Financia Multi Finance Palopo Branch as a sample. Design/methodology/approach - This quantitative study uses associativity or relationships between variables. The goal is to find out how three or more variables relate to each other. This research was conducted at PT. KB Financia Multi Finance Palopo Branch, with 58 employees as samples. The sampling method is purposive. The data analysis technique in this research begins by conducting instrument tests, namely validity and reliability tes. Finding - The results of this research show that the work engagement variable is significant on employee performance. The work-life balance variable is positive and significant on employee performance at PT. KB Financia Multi Finance Palopo Branch. Work engagement and work-life balance simultaneously influence the performance of PT employees. KB Financia Multi Finance Palopo Branch. Originality - The research results show that employee performance is significantly influenced by work-life balance. Lockwood's work-life balance theory describes work-life balance as when a person can organize and divide his responsibilities between work, family life, and other responsibilities so that there is no conflict between family life and work.